Experimental behavior of wood flooring systems - Penner, Bryant Grant, author; Criswell, M. E., author; Bodig, J., author; Goodman, J. R., author; Vanderbilt, M. D., author; Civil Engineering Department, Colorado State University, publisher (Colorado State University. Libraries, 1972)
The main objective of the overall project which included this study is to develop a mathematical model of wood joist floor systems which incorporates the T-beam action between the joists and plywood sheathing and the effect of inter-layer slip. Results of tests of wood flooring systems which were constructed and load tested to verify the deflections computed from the mathematical models are presented. Mathematical variations within these floors included joist size and species, plywood species and thickness, and type of nails. Test results showed that concentrated loads of up to eight times that considered allowable by conventional design could be carried before failure of the first joist. It was also found that an average of 300 percent more load could be supported without exceeding deflection limitations assumed in conventional methods of analysis. This report contains a description of the construction and loadtesting of wood flooring systems and T-beams. The T-beams were built to study the effects that a plywood flange attached to the joists had on the strength and stiffness of the floor system. The strains within the plywood flange were measured at several load increments by strain gage transducers attached to the plywood decking. An effective flange width can then be assumed from these strains measured within the plywood flange. Joist deflections were also recorded for various load increments and positions. By comparing T-beam joist deflections with and without the plywood flange attached for one T-beam, a 34 percent increase in stiffness could be attributed directly to the composite T-beam action of the plywood (for the range of variables considered).
CER72-73BGP-MEC-JB-JRG-MOV26.
December, 1972.
Circulating copy deaccessioned 2020.
Keywords: Flooring, Wooden